Umbilical cord derived mesenchymal stem cell therapy for osteoarthritis: a consolidated review - Zuo, Jianwei; Chen, Chen; Zhang, Xintao; Zhang, Wentao (Penerbit Universiti Kebangsaan Malaysia, 2020)
Osteoarthritis (OA) is a leading cause of degenerative disease and is the most common persistent condition worldwide. The common burden imposed by OA significantly damages the articular cartilage, which results in pain and seriously impacts the quality of life in the affected people. Disease progression is assumed to increase with obesity and aging. The current therapies include weight loss, activity adjustment, traditional pain management and replacement of the affected joint. To overcome these limitations, recently, cell-based therapies mainly Umbilical cord derived Mesenchymal stem cell (UC-MSC) have become an attractive cell source for an allogeneic mesenchymal stem cell to repair and regenerate the structure and function of articular tissues. Although the mechanism is not clearly defined, it is believed that the paracrine signaling, inflammatory response, and immunomodulatory role of UC-MSCs play a crucial role in developing a treatment approach of OA. The purpose of this review was to outline the advantages of using UC-MSCs in treating OA. This review also discusses the possible hurdles that stand in the way of successful implementation of UC-MSC as a routine treatment regimen for OA.